Upaya pencegahan risiko LGBT pada remaja SMA (LGBT risk prevention efforts in Senior High School adolescents) - Esi Afriyanti; Elvi Oktarina; Feri Fernandes (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2018)
The problem of lesbian, gay, bisexual and transgender, or known as LGBT, has becomeprominent in the world in more than a decade. This problem is also a concern in Indonesia alongwith the rise of HIV cases. From 1990 to 2016 there was an increase in HIV and AIDS caseswhere an increase in HIV AIDS cases was transmitted by heterosexual sexual activity.Heterosexual is mostly done by LGBT people. Most homosexuals (Lesbian, Gay andtransgender) begin to realize that they have different tendencies when they are young. Studiesshow homosexual behavior and same-sex attraction have been encountered since the age of 15.This situation shows that the school age group is the age of the vulnerable to start engaging insame-sex relationships. While the decision to become homosexual or majadi lesbian occursmostly in young adults or at the age when they are already students. For this reason, early prevention of LGBT is needed. This prevention can be done by early detection of the tendencyfor sexual behavior and health education about its impact on life. Besides this early preventioncan be done with role play in adolescents so that adolescents can analyze how LGBT preventionis. This community service was held on Saturday, November 27, 2018 with a total of 76participants. Counseling was conducted at SMAN 9 Padang in class XI. The method used inthis activity was counseling and health education with the lecture method, role play involvingstudents and also effective teachers in schools by providing booklets and leaflets which wereone of the means to increase the knowledge of teachers and students about LGBT. The existenceof booklets and information leaflets will be conveyed systematically.